Symbol

# Calculator search results

Formula
Solve the quadratic equation
Answer
Number of solution
Answer
Relationship between roots and coefficients
Answer
Graph
$y = x ^ { 2 } + x + \dfrac { 1 } { 2 }$
$y = 0$
$y$Intercept
$\left ( 0 , \dfrac { 1 } { 2 } \right )$
Minimum
$\left ( - \dfrac { 1 } { 2 } , \dfrac { 1 } { 4 } \right )$
Standard form
$y = \left ( x + \dfrac { 1 } { 2 } \right ) ^ { 2 } + \dfrac { 1 } { 4 }$
$x ^{ 2 } +x+ \dfrac{ 1 }{ 2 } = 0$
$\begin{array} {l} x = \dfrac { - 1 + i } { 2 } \\ x = \dfrac { - 1 - i } { 2 } \end{array}$
Solve quadratic equations using the square root
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = 0$
 Calculate the expression as a fraction format 
$\color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = 0$
$\color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = \color{#FF6800}{ 0 }$
 Multiply both sides by the least common multiple for the denominators to eliminate the fraction 
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }$
 Divide both sides by the coefficient of the leading highest term 
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = \color{#FF6800}{ 0 }$
$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 1 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = \color{#FF6800}{ 0 }$
 Convert the quadratic expression on the left side to a perfect square format 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ 0 }$
$\left ( x + \dfrac { 1 } { 2 } \right ) ^ { 2 } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ - } \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = 0$
 Move the constant to the right side and change the sign 
$\left ( x + \dfrac { 1 } { 2 } \right ) ^ { 2 } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ + } \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
$\left ( x + \dfrac { 1 } { 2 } \right ) ^ { 2 } = - \dfrac { 1 } { 2 } + \left ( \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } }$
 When raising a fraction to the power, raise the numerator and denominator each to the power 
$\left ( x + \dfrac { 1 } { 2 } \right ) ^ { 2 } = - \dfrac { 1 } { 2 } + \dfrac { \color{#FF6800}{ 1 } ^ { \color{#FF6800}{ 2 } } } { \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 ^ { 2 } } { 2 ^ { 2 } } }$
 Organize the expression 
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 4 } }$
$\left ( \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } \right ) ^ { \color{#FF6800}{ 2 } } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 4 } }$
 Solve quadratic equations using the square root 
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 4 } } }$
$\color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 4 } } }$
 Solve a solution to $x$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { i } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
$\color{#FF6800}{ x } = \pm \color{#FF6800}{ \dfrac { i } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } }$
 Separate the answer 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { i } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { i } { 2 } } \end{array}$
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { i } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 1 } { 2 } } \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { i } { 2 } } \end{array}$
 Organize the expression 
$\begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 1 + i } { 2 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 1 - i } { 2 } } \end{array}$
$\begin{array} {l} x = \dfrac { - 1 + i } { 2 } \\ x = \dfrac { - 1 - i } { 2 } \end{array}$
Calculate using the quodratic formula$($Imaginary root solution$)$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = 0 $Calculate the expression as a fraction format$ \color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = 0\color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = \color{#FF6800}{ 0 } $Multiply both sides by the least common multiple for the denominators to eliminate the fraction$ \color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 } $Solve the quadratic equation$ ax^{2}+bx+c=0 $using the quadratic formula$ \dfrac{-b\pm\sqrt{b^{2}-4ac}}{2a}\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 2 \times 1 } } { 2 \times 2 } }\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ 2 ^ { 2 } - 4 \times 2 \times 1 } } { 2 \times 2 } } $Organize the expression$ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ - 4 } } { 2 \times 2 } }x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 4 } } } { 2 \times 2 } $Organize the part that can be taken out of the radical sign inside the square root symbol$ x = \dfrac { - 2 \pm \color{#FF6800}{ 2 } \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 1 } } } { 2 \times 2 }x = \dfrac { - 2 \pm 2 \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 1 } } } { 2 \times 2 } $It is$ \sqrt{-1} = ix = \dfrac { - 2 \pm 2 \color{#FF6800}{ i } } { 2 \times 2 }x = \dfrac { - 2 \pm 2 i } { \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } } $Multiply$ 2 $and$ 2x = \dfrac { - 2 \pm 2 i } { \color{#FF6800}{ 4 } }\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm 2 i } { 4 } } $Separate the answer$ \begin{array} {l} \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 + 2 i } { 4 } } \\ \color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 - 2 i } { 4 } } \end{array}\begin{array} {l} x = \color{#FF6800}{ \dfrac { - 2 + 2 i } { 4 } } \\ x = \dfrac { - 2 - 2 i } { 4 } \end{array} $Reduce the fraction$ \begin{array} {l} x = \color{#FF6800}{ \dfrac { - 1 + i } { 2 } } \\ x = \dfrac { - 2 - 2 i } { 4 } \end{array}\begin{array} {l} x = \dfrac { - 1 + i } { 2 } \\ x = \color{#FF6800}{ \dfrac { - 2 - 2 i } { 4 } } \end{array} $Reduce the fraction$ \begin{array} {l} x = \dfrac { - 1 + i } { 2 } \\ x = \color{#FF6800}{ \dfrac { - 1 - i } { 2 } } \end{array} $Do not have the solution$ $Calculate using the quadratic formula$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = 0 $Calculate the expression as a fraction format$ \color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = 0\color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = \color{#FF6800}{ 0 } $Multiply both sides by the least common multiple for the denominators to eliminate the fraction$ \color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 1 } } { 2 \times 2 } $Calculate power$ x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ 4 } - 4 \times 2 \times 1 } } { 2 \times 2 }x = \dfrac { - 2 \pm \sqrt{ 4 - 4 \times 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } } } { 2 \times 2 } $Multiplying any number by 1 does not change the value$ x = \dfrac { - 2 \pm \sqrt{ 4 - 4 \times 2 } } { 2 \times 2 }x = \dfrac { - 2 \pm \sqrt{ 4 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } } } { 2 \times 2 } $Multiply$ - 4 $and$ 2x = \dfrac { - 2 \pm \sqrt{ 4 \color{#FF6800}{ - } \color{#FF6800}{ 8 } } } { 2 \times 2 }x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 8 } } } { 2 \times 2 } $Subtract$ 8 $from$ 4x = \dfrac { - 2 \pm \sqrt{ \color{#FF6800}{ - } \color{#FF6800}{ 4 } } } { 2 \times 2 }x = \dfrac { - 2 \pm \sqrt{ - 4 } } { \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } } $Multiply$ 2 $and$ 2x = \dfrac { - 2 \pm \sqrt{ - 4 } } { \color{#FF6800}{ 4 } }\color{#FF6800}{ x } = \color{#FF6800}{ \dfrac { - 2 \pm \sqrt{ - 4 } } { 4 } } $The square root of a negative number does not exist within the set of real numbers$  $Do not have the solution$  $Do not have the real root$ $Find the number of solutions$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = 0 $Calculate the expression as a fraction format$ \color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = 0\color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = \color{#FF6800}{ 0 } $Multiply both sides by the least common multiple for the denominators to eliminate the fraction$ \color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 } $Determine the number of roots using discriminant,$ D=b^{2}-4ac $from quadratic equation,$ ax^{2}+bx+c=0\color{#FF6800}{ D } = \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ 1 }D = \color{#FF6800}{ 2 } ^ { \color{#FF6800}{ 2 } } - 4 \times 2 \times 1 $Calculate power$ D = \color{#FF6800}{ 4 } - 4 \times 2 \times 1D = 4 - 4 \times 2 \color{#FF6800}{ \times } \color{#FF6800}{ 1 } $Multiplying any number by 1 does not change the value$ D = 4 - 4 \times 2D = 4 \color{#FF6800}{ - } \color{#FF6800}{ 4 } \color{#FF6800}{ \times } \color{#FF6800}{ 2 } $Multiply$ - 4 $and$ 2D = 4 \color{#FF6800}{ - } \color{#FF6800}{ 8 }D = \color{#FF6800}{ 4 } \color{#FF6800}{ - } \color{#FF6800}{ 8 } $Subtract$ 8 $from$ 4D = \color{#FF6800}{ - } \color{#FF6800}{ 4 }\color{#FF6800}{ D } = \color{#FF6800}{ - } \color{#FF6800}{ 4 } $Since$ D<0 $, there is no real root of the following quadratic equation$  $Do not have the real root$ \alpha + \beta = - 1 , \alpha \beta = \dfrac { 1 } { 2 }$Find the sum and product of the two roots of the quadratic equation$\color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ \dfrac { 1 } { 2 } } = 0 $Calculate the expression as a fraction format$ \color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = 0\color{#FF6800}{ \dfrac { 2 x ^ { 2 } + 2 x + 1 } { 2 } } = \color{#FF6800}{ 0 } $Multiply both sides by the least common multiple for the denominators to eliminate the fraction$ \color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 }\color{#FF6800}{ 2 } \color{#FF6800}{ x } ^ { \color{#FF6800}{ 2 } } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 1 } = \color{#FF6800}{ 0 } $In the quadratic equation$ ax^{2}+bx+c=0 $, if the two roots are$ \alpha, \beta $, then it is$ \alpha + \beta =-\dfrac{b}{a} $,$ \alpha\times\beta=\dfrac{c}{a}\color{#FF6800}{ \alpha } \color{#FF6800}{ + } \color{#FF6800}{ \beta } = \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 2 } } , \color{#FF6800}{ \alpha } \color{#FF6800}{ \beta } = \color{#FF6800}{ \dfrac { 1 } { 2 } }\alpha + \beta = - \color{#FF6800}{ \dfrac { 2 } { 2 } } , \alpha \beta = \dfrac { 1 } { 2 } $Reduce the fraction$ \alpha + \beta = - \color{#FF6800}{ 1 } , \alpha \beta = \dfrac { 1 } { 2 }\$
Have you found the solution you wanted?
Try again
Try more features at Qanda!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture